2015
DOI: 10.1016/j.hlc.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immediate and Long-term Results between the Single Balloon and Inoue Balloon Techniques for Percutaneous Pulmonary Valvuloplasty

Abstract: Adults can be treated with BPV using the Inoue balloon with encouraging immediate and long-term follow-up results that are similar to those in children using the single balloon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…The decreases in our patients' gradients were similar to those after BPV with other types of balloons. [5][6][7][8]10 Early after treatment, all of our patients had residual systolic gradients, but these continued to improve during the followup period. All 3 patients were prescribed β-adrenergic blocker therapy after intervention; it was useful in each case, but was especially beneficial to Patients 1 and 2 because of their infundibular hypertrophy and presumed systolic gradient contributing to RV and PA stenosis.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The decreases in our patients' gradients were similar to those after BPV with other types of balloons. [5][6][7][8]10 Early after treatment, all of our patients had residual systolic gradients, but these continued to improve during the followup period. All 3 patients were prescribed β-adrenergic blocker therapy after intervention; it was useful in each case, but was especially beneficial to Patients 1 and 2 because of their infundibular hypertrophy and presumed systolic gradient contributing to RV and PA stenosis.…”
Section: Discussionmentioning
confidence: 65%
“…4 The Inoue balloon reportedly improves hemodynamics; however, it is compliant, and it loses its hourglass shape during maximal inf lation, which places the PV annulus, the STJ, and the leaf lets at risk of rupture. 7,8,[10][11][12] Moreover, it can be difficult to manipulate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Liu et al reported that about 20% had mild pulmonary regurgitation after the procedure immediately and most mild Pulmonary regurgitation kept stable except one patients developed to severe pulmonary regurgitation in the long-term observation. 12 However, Merino-Ingelm et al reported that almost all the patients in their study suffered different grade of pulmonary regurgitation at 10 years follow-up, suggesting that pulmonary regurgitation increases and becomes more severe over the follow-up. 13 In the present study, pulmonary regurgitation occurred in six patients (17.6%, sight 14.7%, mild 2.9%) after the procedure.…”
Section: Resultsmentioning
confidence: 76%
“…7 The children group had a right ventriclepulmonary artery (RV-PA) systolic gradient of 52.79±35.08 mm of Hg that decreased to 22.55±12.92 mm of Hg following BPV (P <0.001). None of the children who underwent graded dilation developed evidence of serious complications.…”
Section: Discussionmentioning
confidence: 95%